147k views
22 votes
Anyone knows this please help me

Anyone knows this please help me-example-1
User Abdu
by
5.8k points

1 Answer

3 votes

Answer:

(0, 2 ) and (-
(4)/(3),
(2)/(9) )

Explanation:

Given the 2 equations

2x² + 4x - y = - 2 → (1)

x² + y = 2 → (2)

subtract x² from both sides in (2)

y = 2 - x² → (3)

Substitute y = 2 - x² into (1)

2x² + 4x - (2 - x²) = - 2

2x² + 4x - 2 + x² = - 2

3x² + 4x - 2 = - 2 ( add 2 to both sides )

3x² + 4x = 0 ← in standard form

x(3x + 4) = 0 ← in factored form

Equate each factor to zero and solve for x

x = 0

3x + 4 = 0 ⇒ 3x = - 4 ⇒ x = -
(4)/(3)

Substitute these values into (3) for corresponding values of y

x = 0 : y = 2 - 0² = 2 - 0 = 2 ⇒ (0, 2)

x = -
(4)/(3) : y = 2 - (-
(4)/(3) )² = 2 -
(16)/(9) =
(2)/(9) ⇒ ( -
(4)/(3),
(2)/(9) )

User BenRI
by
6.4k points